Principles for optimizing the composition of a complex of machines for cleaning and restoring reclamation canals - Kh. A. Abdulmazhidov (Овощи России, 2022)
The article is devoted to the principles of optimizing the composition of the complex of machines for cleaning the reclamation channels of the drainage network The fundamental initial documents in determining the composition of the complex of machines for the production of operational, repair and restoration works are technological maps for carrying out repair measures to restore the reclamation channels of the drainage system. Technological maps are formed taking into account the requirements for the elements of the drainage system, due to the specific conditions of the zone of economic regions, the natural and production characteristics of reclamation facilities.